2017
DOI: 10.3892/etm.2017.5254
|View full text |Cite
|
Sign up to set email alerts
|

miR‑34a and miR‑125b are upregulated in peripheral blood mononuclear cells from patients with type 2 diabetes mellitus

Abstract: Abstract. Type 2 diabetes mellitus (T2DM) is a leading cause of blindness, non-traumatic amputation and end-stage renal disease, as well as a major cardiovascular risk factor. To determine whether miR-125b and miR-34a serve an important role in the development of T2DM, the current study investigated the expression profile of two microRNAs (miR-34a and miR-125b) and their relative genes in peripheral blood mononuclear cells from 73 patients with T2DM and 52 healthy donors by reverse transcription-quantitative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 52 publications
5
24
0
Order By: Relevance
“…A similar increase in senescence of the smooth muscle that surrounds pulmonary arteries in these patients was also observed, providing further links between vascular senescence, atherosclerosis and COPD [69]. Small sections of regulatory RNA, known as microRNAs (miRs) have been implicated in promoting cellular senescence and miR-34a has been associated with fibroblast senescence in COPD [70] atherosclerosis [71] and T2D [72], demonstrating a common link between diseases.…”
Section: Theme 1: Accelerated Ageing In Multimorbiditysupporting
confidence: 55%
“…A similar increase in senescence of the smooth muscle that surrounds pulmonary arteries in these patients was also observed, providing further links between vascular senescence, atherosclerosis and COPD [69]. Small sections of regulatory RNA, known as microRNAs (miRs) have been implicated in promoting cellular senescence and miR-34a has been associated with fibroblast senescence in COPD [70] atherosclerosis [71] and T2D [72], demonstrating a common link between diseases.…”
Section: Theme 1: Accelerated Ageing In Multimorbiditysupporting
confidence: 55%
“…miR-34a is a well characterized regulator of sirtuin 1 (SIRT1) [49] and studies demonstrate that inhibition of miR-34a can ameliorate altered glucose metabolism, obesity and steatosis by restoring SIRT1 and peroxisome proliferator-activated receptor α (PPARα) signaling [94] and β-Klotho/Fibroblast growth factor-19 signaling [95,96]. In line with previous studies [97][98][99], our results also show a significantly upregulated expression of miR-34a in patients with obesity, diabetes and fatty infiltration, which can be used as a biomarker for disease progression. Similarly, miR-375, is a key regulator of glucose homeostasis, lipid metabolism, inflammatory response and insulin resistance under various metabolic stress conditions and is found to be upregulated in the circulation during obese, diabetic, simple steatosis and NASH [50,100,101].…”
Section: Discussionsupporting
confidence: 79%
“…Notably miR-125b is a member of the miR-17-92 cluster and has been demonstrated to function as an oncomir in numerous human cancer types. A study performed by Wang et al (18) demonstrated that miR-125b was highly expressed in breast cancer and Shen et al (19) reported that miR-125b expression was markedly increased in type 2 diabetes mellitus. Previous research has also demonstrated that high levels of miR-125b was associated with shortened progression-free survival times (20).…”
Section: Discussionmentioning
confidence: 99%